Gaya Kepemimpinan Kepala Sekolah DalamMeningkatkan Kinerja Guru Di Sman 1 Bulu - Avisha, Andri; , Dr. Ari Anshori.M.Ag (2017)
Leadership is the process of influencing the activities of a group in the organization, leading to the determination / achievement of objectives. The school principal has a very important role as a leader in moving the school to achieve it's goal. The principal function is to instill influence to teachers so that they perform their duties wholeheartedly and enthusiastically. Of teachers have an important role in determining the effectiveness of the learning process and the achievement of the objectives of the school, so that teachers are required to be able to show optimal performance. The level of achievement of the teacher's performance can not be separated from the influence of the principal's leadership style. In this study, the considered problem is what leadership style applied by the principal of SMAN 1 Bulu? And how does the principal improve teacher performance in SMAN 1 Bulu? The purpose of this study is to describe the style of principal leadership and his efforts in improving teacher performance. The benefit of this research is to give contributions in improving the performance of teachers as a provision for principals in an effort to improve teacher performance. This type of research is the study field. The source data is the principal as well as documents. Collecting data uses interviews, observation, and documentation. Meanwhile the method of data analysis uses qualitative inductive description. Based on the analysis of research data, it can be concluded that the style of school leadership in improving the performance of teachers at SMAN 1 Bulu uses three styles of leadership, namely: democratic leadership style, authoritarian leadership style and, situational contingency leadership style. As for efforts in improving the performance of the school head teacher at SMAN 1 Bulu: 1. Guidance to teachers and staff at the school for teacher and employees performance can be increased; 2. Conduct regular evaluation once every week so that the performance has not been good teacher can increase; 3. Provide a good motivation for the performance of teachers and employees can be increased. Keywords: headmaster, leadership, Performance